A systematic review of persuasive marketing techniques to promote food to children on television. Issue 4 (17th January 2014) - Jenkin, G.; Madhvani, N.; Signal, L.; Bowers, S.
Summary The ubiquitous marketing of energy‐dense, nutrient‐poor food and beverages is a key modifiable influence on childhood dietary patterns and obesity. Much of the research on television food advertising is focused on identifying and quantifying unhealthy food marketing with comparatively few studies examining persuasive marketing techniques to promote unhealthy food to children. This review identifies the most frequently documented persuasive marketing techniques to promote food to children via television. A systematic search of eight online databases using key search terms identified 267 unique articles. Thirty‐eight articles met the inclusion criteria. A narrative synthesis of the reviewed studies revealed the most commonly reported persuasive techniques used on television to promote food to children. These were the use of premium offers, promotional characters, nutrition and health‐related claims, the theme of taste, and the emotional appeal of fun. Identifying and documenting these commonly reported persuasive marketing techniques to promote food to children on television is critical for the monitoring and evaluation of advertising codes and industry pledges and the development of further regulation in this area. This has a strong potential to curbing the international obesity epidemic besieging children throughout the world.